Whistleblowing and power: A network perspective. (25th June 2020) - Thomas, R. Guy
Abstract: This article presents a network perspective on whistleblowing. It considers how whistleblowing affects, and is affected by, the preexisting distribution of power inside and outside an organization, where power is conceptualized as deriving from the network positions of the key actors. The article also highlights four characteristic features of whistleblowing: third‐party detriment, local subversion, appeal to central or external power, and reasonable expectation of concern. The feature of local subversion succinctly explains why whistleblowing is difficult. The feature of appeal to central or external power highlights that contrary to the perception of a democratizing phenomenon, whistleblowing tends to redistribute discretion away from local power toward more central power. This suggests a need for caution about institutional measures to promote whistleblowing in contexts where governance is already highly centralized.